Why do elephants destroy woodland? [Commentt 2] [letter to the editor] - Robert Olivier (Pachyderm)
Refers to the article by Jachmann and Bell in the previous issue, no 3 p9-10, and notes because of both nutritional needs and the fact that elephants are a ecotone species between forest and grasslands they are both browsers and grazers. Suggests changes are part of ecology and as such an long term equilibria between elephants and woodland is not a feasible concept.